The application of value stream mapping in a food-based industry - Siti Khadijah Zulkefli (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Unnecessary movement of worker is one of seven sources of waste. This project was conducted in order to reduce unnecessary movement during the ptoduction of 2in1 green coffee by applying Value StreamMapping at thr coffee maker company. This project will focus in the packaging area where unnecessary movement occur during the packaging process. The flow of process during packaging is abserved and is recprd in the current Value Stream Mapping. Based on the observation,